2009
DOI: 10.1074/jbc.m109.032904
|View full text |Cite
|
Sign up to set email alerts
|

MqsR, a Crucial Regulator for Quorum Sensing and Biofilm Formation, Is a GCU-specific mRNA Interferase in Escherichia coli

Abstract: The mqsR gene has been shown to be positively regulated by the quorum-sensing autoinducer AI-2, which in turn activates a two-component system, the qseB-qseC operon. This operon plays an important role in biofilm formation in Escherichia coli. However, its cellular function has remained unknown. Here, we found that 1 base downstream of mqsR there is a gene, ygiT, that is co-transcribed with mqsR. Induction of mqsR caused cell growth arrest, whereas ygiT co-induction recovered cell growth. We demonstrate that M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
180
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(191 citation statements)
references
References 56 publications
10
180
1
Order By: Relevance
“…Threshold regulation of phenotypic variability may be a general property of those motifs, whose function would be to differentiate bacterial populations into distinct subpopulations to cope with stress (21). Recent evidence that implicates TA modules in Myxococcus development (43) and in biofilm formation (44,45) support that view. Finally, through linking a genetic regulatory motif and its phenotypic effect, we now have a basic understanding of the connections between multiple elements of bacterial persistence: genotype, phenotype, and fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Threshold regulation of phenotypic variability may be a general property of those motifs, whose function would be to differentiate bacterial populations into distinct subpopulations to cope with stress (21). Recent evidence that implicates TA modules in Myxococcus development (43) and in biofilm formation (44,45) support that view. Finally, through linking a genetic regulatory motif and its phenotypic effect, we now have a basic understanding of the connections between multiple elements of bacterial persistence: genotype, phenotype, and fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we determined the crystal structures of MqsA alone and the MqsR⅐MqsA complex and showed that the mqsRA operon defines a novel family of TA systems in E. coli, in which MqsR is the toxin and MqsA is the antitoxin (19). The structure revealed that the MqsR toxin is a ribonuclease belonging to the RelE bacterial toxin family (19,34,35). MqsR is unique because it is the first toxin linked to biofilms and quorum sensing (33) and is the first toxin that, when deleted, decreases persister cell formation (31).…”
mentioning
confidence: 99%
“…The antitoxin MqsA is even more unusual because it is the first antitoxin that requires a metal, zinc, for structural stability (19); it is the only E. coli antitoxin that is structured throughout its entire sequence; and it is the first antitoxin demonstrated to bind DNA via its C-terminal and not N-terminal domain (19, 27, 36 -39). Critically, in addition to binding its own promoter (19,34,35,40), MqsA and the MqsR⅐MqsA complex are also the only known antitoxin/TA pair that bind not only their own promoter but also the promoters of other genes that play important roles in E. coli physiology, including mcbR and spy (19) as well as cspD (31). Moreover, although 14 antitoxin structures have been solved to date, their primary sequences are highly divergent when compared with MqsA (supplemental Table S1) because the sequence identity between MqsA and the most closely related antitoxin, the E. coli protein HigA, is only 13%.…”
mentioning
confidence: 99%
“…In view of all this, we argued that Kid and Kis functioned as a rescue system for plasmid R1, and not as a PSK system (24). This proposal cannot be supported by results elsewhere, suggesting that Kid may cleave mRNA at simpler UAH sites (with H being A, C, or U) (25,26), a view that has prevailed in the literature (14,16,(27)(28)(29). Moreover, other observations indicate that our past experiments may have been inappropriate to conclude that Kid does not kill Escherichia coli cells (30,31).…”
Section: Significancementioning
confidence: 68%
“…24 and below). Because the notion that Kid cleaves mRNAs at UA(A/C/U) (14,27), UA(A/C) (28), or UAC (16, 29) prevailed, we decided to investigate this issue in more detail. Resumption of cell growth in Fig.…”
Section: Kid Inhibits Cell Division In E Coli and Does Not Halt Protmentioning
confidence: 99%